Some theorems concerning the characterization of gamma-distribution and near to it ones - Kagan, F. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ф. М. Каган. Некоторые теоремы о характеризации гамма-распределения и близких к немуF. Kaganas. Keletas teoremų apie gama ir jam artimų pasiskirstymo dėsnių charakterizavimą